The Role of the Community and Village Empowerment Office in Improving the Development Village Index - febriani, fika; Paisal Topan Nugraha; Ida Noviyanti; Ikhtia Faizatuz Zahrah; Dio Alip Fadilla; Regi Refian Garis (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This research aims to understand the role of the Ciamis Regency Community and Village Empowerment Service (DPMD) in increasing the Village Development Index (IDM). IDM is an indicator that reflects village progress in social, economic and ecological aspects. Using a qualitative approach, this research explores various programs and policies implemented by DPMD, as well as the factors that influence their success. The research results show that the Ciamis Regency DPMD has succeeded in increasing village status to